Peningkatan Kesadaran Pengelolaan Sampah melalui Edukasi 3R: Program KKN Tematik di SDN 6 Padangsambian Klod - I Kadek Dwi Fajar Swastika; Komang Widhya Sedana Putra P; IGN Oka Ariwangsa; Kadek Wulandari Laksmi P (Yayasan Inspirasi El Burhani, 2025)
Introduction: The severity of waste management problems on Indonesia especially on waste in Denpasar City, Bali requires immediate attention. This KKN thematic program targeted to increase the knowledge and active involvement of primary school students in waste management using the 3R (Reduce, Reuse, Recycle) approach at SDN 6 Padangsambian Klod. Objective: With this service, we seek to address the issues arising from the school’s lack of awareness of waste management and the low number of waste disposal facilities by implementing educational and practical waste management systems at the school. Method: This public service was carried out by conducting initial observation and interactivity socialization, including the use of educational animated videos, distribution of poster brochures, mono colored paper to facilitate sorting of waste, and bins for each category. Result: The results demonstrated a marked increase in students’ comprehension of the 3R concept, waste types, and waste segregation. Because of the initiatives, students also decreased their usage of single-use items which display positive change in behavior even with time and resource constraints. Conclusion: The goals were successfully finished with the collaboration of KKN students, teachers, and students. Early 3R education is has proven to be effective for nurturing environment-conscious responsible young citizens.